Exploring Instagram Strategies: A Comparative Analysis of DMO in central region of Portugal - Vítor Sá; Lígia Azevedo; José Antonio Fraiz Brea (Investigaciones Turísticas)
Instagram has become one of the principal social media platforms with substantial influence in contemporary society. This study sheds light on the divergent approaches adopted by two DMOs tasked with promoting the central region of Portugal. This approach encompasses several facets, including the types of images shared, the frequency of publication, and the implementation of hashtags. All the images shared by the two accounts in 2022 were systematically collected and subjected to exhaustive analysis based on predetermined parameters. The research revealed different strategies for using Instagram, despite both DMOs promoting the same territory. While the ERTCP account, @centro_de_portugal, focuses mainly on the Nature & Landscape and Place categories, the ARPTCP account, @centerofportugal, emphasises Humanised Spaces and Architecture categories. The frequency of publication and the use of hashtags also varied, with the ERTCP account posting more frequently and using a wider range of hashtags. In terms of engagement metrics, the @centro_de_portugal maintains its prominent position. However, the pattern of follower interaction over the course of the year was similar for both accounts, with the first and last four months witnessing higher engagement. An analysis of the frequency of posts per day of the week also revealed different patterns.